Analysis Of The Incidence Of Stunting, Malnutrition And Undernutrition Among Toddlers In Sari Mulya Village - Cengri - Seluma Regency - Bengkulu Year 2024 - Theresiana, Yunita; Novira, Daisy; Nurdan, Jon Hendri; Pansori, Hartian; Harianja, Firman Bintara Maju (Universitas Dehasen Bengkulu, 2024)
Stunting is a condition of growth failure in children (body and brain growth) or chronic malnutrition due to being malnourished for a long time, resulting in children being shorter than normal children of their age and having delays in thinking. The problem of stunting is still the main focus in handling nutritional problems in Indonesia. Method: This type of research is analytical observational research with a cross-sectional study design. The population and sample in this study were 40 toddlers aged 24-49 months who were taken by accidental sampling. Univariate, bivariate and multivariate data analysis using Chi-square analysis techniques. This research started from April 16 to May 15 2024. Results: The results of the study showed that 24 toddlers (60%) were stunted and 16 toddlers (40%) were not stunted. There is a relationship between the role of health workers (p=0.003), parenting style (p=0.009) and the availability of pediatricians (p=0.021). Conclusion: It is hoped that community health centers can create more constructive programs to minimize risk factors that cause stunting.